Effect of high fat-diet and obesity on gastrointestinal motility - Al Mushref, Mazen (AME Publishing Company, 2013)
Obesity is highly prevalent worldwide and is associated with significant morbidity and mortality. The focus of this review is to delineate the changes in gastrointestinal motility observed in obesity. A systematic review of the published literature on obesity and gastrointestinal motility was performed. Here, we describe the current understanding of the changes in obesity in the esophagus, stomach, small intestine and colon. Major findings include supportive evidence for increased gastroesophageal reflux disease and esophageal motility disorders in obesity, and a rapid gastric emptying time seen in obese individuals. The proximal small intestinal transit seems to be increased in obesity and this may be secondary to efficient nutrient absorption and subsequent lack of nutrient-induced satiety signals conveyed from the small intestine. In obesity, there is some evidence for delayed colonic transit as well as a reduction in colonic serotonin availability. The molecular mechanisms underlying altered motility in obesity could be secondary to reduced cannabinoids or its receptor cannabinoid receptor 1 (CB1) expression as well as due to loss of neuronal nitric oxide synthase (nNOS) neurons. The interactions of diet and obesity and the alteration of microbiota in this setting are just being explored and may offer novel insights into the changes of gastrointestinal motility in obesity.